Sustainable human resource management practices in maritime supply chains - Ugrinov Stefan; Ćoćkalo Dragan; Bakator Mihalj (Održivi razvoj)
This paper explores the implementation of sustainable human resource management practices in maritime supply chains, with a focus on Green Human Resource Management (GHRM), workforce well-being and compliance with global standards. GHRM practices, including the digitalization of HRM processes and energy-efficient operations, are analyzed as key elements for reducing environmental impact while improving operational efficiency. Workforce well-being is addressed through health and safety training, mental health support and efforts to improve work-life balance, which contributes to long-term employee retention and satisfaction. Compliance with international regulations, such as the Maritime Labour Convention (MLC) and International Maritime Organization (IMO) standards, is highlighted as the basis for ethical labour practices and environmental responsibility. The paper suggests strategies for governments, businesses and individuals to contribute to sustainable human resource management, including policy implementation, workforce training and individual engagement. Through joint efforts, the maritime industry can achieve sustainable practices that support environmental goals and the long-term stability of its workforce.